The roots of Texas music - Clayton, Lawrence, 1938-2000; Specht, Joe W., 1945- (Texas A & M University Press, 2003)
Contains nine essays in which the authors examine various aspects of Texas music from its beginnings to 1950, providing an overview of Texas music history, and discussing Texan jazz, country music, early Texas bluesmen, classical and religious music, and various ethnic genres.
Includes index.
Keywords: Music -- Texas -- History and criticism.; Musique -- Texas -- Histoire et critique.; MUSIC -- History & Criticism.; Music; Texas; Musik; Criticism, interpretation, etc.